Pouk v šolski knjižnici s petošolci o prvih slovenskih knjigah - Škrlj, Gregor (Šolska knjižnica, 2020)
The article describes fifth-grade class in the subject Society, where students learn about the first Slovenian books, the Slovenian language and cultural heritage. It is important to plan the classes on a yearly basis and then implement them according to abilities. Fifth-grade classes are created so as to deepen students% knowledge and introduce them to the history of the nation. All theoretical content is thoroughly introduced, with material that is tangible and allows a better understanding of the value and importance of books over time. This is made possible by moving the class, for one hour, to a well-stocked school library.
Keywords: KIZ; knjižnično gradivo; kulturna dediščina; medpredmetno povezovanje; organizacija pouka; šolske knjižnice; učne metode